Question Select the correct answer. What is the value of x in the equation ln (x + 6) – ln (2x – 1) = 1? A. -0.21 B. 0.74 C. 1.35 D. 1.97

Given the: ln(x + 6) – ln(2x – 1) = 1 Using the logarithm rule: ln a – ln b = ln (a/b) ln((x + 6) / (2x – 1)) = 1 ((x + 6) / (2x – 1)) = E ¹ We know, e1 = ²’⁷² ((x + 6) / (2x – 1)) ≈ 2.72 Simplifying we get, (x + 6) = 2.72 (2x – 1) x + 6 = 2.72 (2x) – 2.72 (1) x + 6 = 5.44x – 2.72 8.72 = 4.44x By cross multiplication we get, x = 8.72 / 4.44 x = 1.97 Therefore, the value of x is 1.97. The correct option in the exercise ln (x + 6) – ln (2x – 1) = 1 is alternative “D”. Reply

ln(x + 6) – ln(2x – 1) = 1ln a – ln b = ln (a/b)ln((x + 6) / (2x – 1)) = 1((x + 6) / (2x – 1)) = E ¹e1 = ²’⁷²((x + 6) / (2x – 1)) ≈ 2.72(x + 6) = 2.72 (2x – 1)x + 6 = 2.72 (2x) – 2.72 (1)x + 6 = 5.44x – 2.728.72 = 4.44xx = 8.72 / 4.44x = 1.97correct optionin the exerciseln (x + 6) – ln (2x – 1) =1 is alternative“D”.